Phenology and ecological role of aerobic anoxygenic phototrophs in freshwaters - Villena-Alemany, Cristian; Mujakić, Izabela; Fecskeová, Livia K; Woodhouse, Jason; Auladell, Adrià; Dean, Jason; Hanusová, Martina; Socha, Magdalena; Gazulla, Carlota R; Ruscheweyh, Hans-Joachim; Sunagawa, Shinichi; Silva Kavagutti, Vinicius; et al. (Microbiome, 2024)
BACKGROUND: Aerobic anoxygenic phototrophic (AAP) bacteria are heterotrophic bacteria that supply their metabolism with light energy harvested by bacteriochlorophyll-a-containing reaction centers. Despite their substantial contribution to bacterial biomass, microbial food webs, and carbon cycle, their phenology in freshwater lakes remains unknown. Hence, we investigated seasonal variations of AAP abundance and community composition biweekly across 3 years in a temperate, meso-oligotrophic freshwater lake. RESULTS: AAP bacteria displayed a clear seasonal trend with a spring maximum following the bloom of phytoplankton and a secondary maximum in autumn. As the AAP bacteria represent a highly diverse assemblage of species, we followed their seasonal succession using the amplicon sequencing of the pufM marker gene. To enhance the accuracy of the taxonomic assignment, we developed new pufM primers that generate longer amplicons and compiled the currently largest database of pufM genes, comprising 3633 reference sequences spanning all phyla known to contain AAP species. With this novel resource, we demonstrated that the majority of the species appeared during specific phases of the seasonal cycle, with less than 2% of AAP species detected during the whole year. AAP community presented an indigenous freshwater nature characterized by high resilience and heterogenic adaptations to varying conditions of the freshwater environment. CONCLUSIONS: Our findings highlight the substantial contribution of AAP bacteria to the carbon flow and ecological dynamics of lakes and unveil a recurrent and dynamic seasonal succession of the AAP community. By integrating this information with the indicator of primary production (Chlorophyll-a) and existing ecological models, we show that AAP bacteria play a pivotal role in the recycling of dissolved organic matter released during spring phytoplankton bloom. We suggest a potential role of AAP bacteria within the context of the PEG model and their consideration in further ecological models.
Keywords: biomasa; aerobní bakterie; Freshwaters; PEG model; Microbial seasonal succession; Biomass; Lakes; Bacteria; jezera; Long-term sampling; Bacteria, Aerobic; fototrofní procesy; Photoheterotrophs; Phototrophic Processes; Aerobic anoxygenic phototrophs; Phytoplankton; pufM gene; fytoplankton; Aquatic microbial ecology